Simvastatin Effects on Skeletal Muscle - Larsen, Steen; Stride, Nis; Hey-Mogensen, Martin; Hansen, Christina N.; Bang, Lia E.; Bundgaard, Henning; Nielsen, Lars B.; Helge, Jørn W.; Dela, Flemming (Journal of the American College of Cardiology, 2013)
Glucose tolerance and skeletal muscle coenzyme Q10 (Q10) content, mitochondrial density, and mitochondrial oxidative phosphorylation (OXPHOS) capacity were measured in simvastatin-treated patients (n = 10) and in well-matched control subjects (n = 9). A prevalent side effect of statin therapy is muscle pain, and yet the basic mechanism behind it remains unknown. We hypothesize that a statin-induced reduction in muscle Q10 may attenuate mitochondrial OXPHOS capacity, which may be an underlying mechanism. Plasma glucose and insulin concentrations were measured during an oral glucose tolerance test. Mitochondrial OXPHOS capacity was measured in permeabilized muscle fibers by high-resolution respirometry in a cross-sectional design. Mitochondrial content (estimated by citrate synthase [CS] activity, cardiolipin content, and voltage-dependent anion channel [VDAC] content) as well as Q10 content was determined. Simvastatin-treated patients had an impaired glucose tolerance and displayed a decreased insulin sensitivity index. Regarding mitochondrial studies, Q10 content was reduced (p = 0.05), whereas mitochondrial content was similar between the groups. OXPHOS capacity was comparable between groups when complex I– and complex II–linked substrates were used alone, but when complex I + II–linked substrates were used (eliciting convergent electron input into the Q intersection [maximal ex vivo OXPHOS capacity]), a decreased (p < 0.01) capacity was observed in the patients compared with the control subjects. These simvastatin-treated patients were glucose intolerant. A decreased Q10 content was accompanied by a decreased maximal OXPHOS capacity in the simvastatin-treated patients. It is plausible that this finding partly explains the muscle pain and exercise intolerance that many patients experience with their statin treatment.